Prevalência de sintomas depressivos em estudantes da área da saúde: revisão integrativa da literatura - OLIVEIRA, Márcia Pena de (2019)
We present a study on the prevalence of depressive symptoms in the health area, and it is not an academic community, but a community in general. . The results obtained through the research in the Virtual Health Library (VHL), with pre-selected key words, obtaining studies indexed in the database. LILACS, MEDLINE, SCIELO and others, between 2005 and 2015. A collection of data provided through the application of a previously prepared instrument. From the inclusion and exclusion criteria, 18 (eighteen) publications were included in the study. It was found that the studied population needs attention, since the students of the health area presented a number of contact points of depression pressures higher than the nonBeck Depression Inventory. These data are very significant, since they point high of depressive symptoms that suggests a high probability of disengagement or a presence of depression. Thus, the implementation of programs of psychological support to students, developed from programs of psychological support to students, developed programs of psychological support to students, developed programs of psychological support to students, developing programs of psychological support to students, developing programs of support for students. Please inform us about the mental health of university students and the concern for their well-being, we suggest continuity of this study and research in the institutions of basic education. It is also interesting to publicize more clearly the psychological support service of students in order to increase security in the search for care.